Semi-Natural Breeding of Philemon buceroides as a Conservation Solution - Yamin, M.; Khairuddin, Khairuddin; Artayasa, I Putu (Jurnal Biologi Tropis, 2025)
The Philemon buceroides is a bird with a limited distribution in the Wallacea region that is difficult to breed in captivity. Its population has drastically declined due to habitat degradation and hunting. This study aims to find its breeding strategies to support its survival. The research was conducted in a breeding cage measuring 4m x 16m x 4.5m, resembling natural habitat conditions. Observed parameters included reproductive success, chick survival rates, and behavioral adaptation of the birds to a semi-natural environment. Results showed that out of four female parents, two succeeded in laying two eggs each; however, the eggs did not contain zygotes. These findings indicate that semi-natural breeding needs to be developed as an effective conservation strategy for P. buceroides, while also providing a scientific basis for the development of long-term release programs.